Using Android Mobile Application for Controlling Green House (Texas Journal of Engineering and Technology, 2022)
The existing system has the ability to yet lack the ability to control indoor humidity. Green House Monitoring and Controlling is a complete system designed to monitor and control the humidity inside a green house. This software uses an Android mobile phone, connected using Wifi to a central server which connects via serial communication to a microcontroller and humidity sensor. The result shows that thecondition specified in sensor’s datasheet and system in reality is appropriate. The achieved test result concludes that the system is working properly